Changes in HDL-c concentrations after 16 weeks of combined training in postmenopausal women: Characteristics of positive and negative responders - Diniz, Tiego A.; Rossi, Fabricio E. [UNESP]; Fortaleza, Ana Claudia Souza [UNESP]; Neves, Lucas Melo [UNESP]; Christofaro, Diego Giulliano Destro [UNESP]; Buonani, Camila [UNESP]; Lira, Fabio S. [UNESP]; Campos, Eduardo Zapaterra [UNESP]; Do Prado, Wagner Luiz; Freitas, Ismael Forte [UNESP] (Canadian Science Publishing, 2018)
This study aimed to investigate the individual characteristics of body composition and metabolic profile that could explain interindividual variation in high-density lipoprotein cholesterol (HDL-c) concentrations in response to 16 weeks of combined strength plus aerobic (combined) training in postmenopausal women. The participants were divided into tertiles based on percentage of changes in HDL-c concentrations after combined training. Only women in the upper tertile (positive responders: Δ > 10.4%; n = 19) and lower tertile (negative responders:Δ< -1.4%; n = 19) were considered for analyses. The total body fat (BF), trunk fat (TF), android fat (AF), gynoid fat, and lean body mass were estimated by dual-energy X-ray absorptiometry. The metabolic profile - glucose, triacylglycerol, total cholesterol, HDL-c, low-density lipoprotein cholesterol, and very-low-density lipoprotein (VLDL) - were assessed. After 16 weeks, both positive and negative responders presented similar improvement in body composition, such as a decrease in percentage and kilograms of BF, TF, and AF, and increase in lean body mass (p value for time < 0.05). As expected, there was an effect of time and also a significant interaction (time vs. group) (p value < 0.001) in the improvement of HDL-c, with higher values for positive responders. Regarding metabolic profile, there were significant interactions (time vs. group) for triacylglycerol (p value = 0.032) and VLDL (p value = 0.027) concentrations, with lower values for positive responders. Our results suggests there is heterogeneity in combined training-induced HDL-c changes in postmenopausal women, and the positive responders were those who presented more pronounced decreases in triacylglycerol and VLDL concentrations.
Keywords: Aerobic exercise; Body composition; High-density lipoprotein; Lipid metabolism; Strength training